Full out : lessons in life and leadership from America's favorite coach - Aldama, Monica, 1970- (Gallery Books, 2022)
"From a woman known as "the Bill Belichick of cheerleading" (The Cut)-the breakout star of the Netflix series, CHEER-a motivational and inspiring guide to becoming a champion in all areas of your life. In FULL OUT, the breakout star of Netflix's CHEER, Monica Aldama, shows how she built one of the most successful, beloved-and now also the most famous-cheerleading programs in the country. Coach Monica tells her story and shares her advice on leadership, achievement, resilience, and success. Her approach goes beyond the mat-showing how the principles of building a winning cheer team apply to the corporate world, parenting, and all aspects of life. Whatever your field, the same principles apply: trust, hard work, discipline, community, consistency. There's a lot of talk these days about short cuts and life hacks, but as the funny, moving stories in FULL OUT reveal, what really counts is commitment, integrity, helping your friends, and improving together with your teammates.Through deeply personal stories of triumph and tragedy, from the divorce and remarriage to her husband, her challenges as a young mother working full time, as well as the students she had to kick off her team, Coach Monica unique form of perseverance is revealed. FULL OUT will show you how to take command of your talent, make the most of your potential, and find the drive to win"--